Spatially Enabled society - Enemark, Stig; Rajabifard, Abbas (Geoforum Perspektiv, 2012)
The term ‘spatially enabled society’ describes the emerging cultural and governance revolution offered by pervasive spatial information technologies and spatially equipped citizens. Spatially enabled societies make possible, amongst many other things, sustainable cities,early warning systems e.g. in relation to the global financial crisis, smarter delivery of housing, improved risk management, and better macroeconomic decision making. This article introduces the current international discussion around the evolving concept of ‘spatially enabled society’. The concept is not about managing spatial information - it is about managing information, or governing society, spatially.